Análise multivariada da estabilidade osmótica de eritrócitos em indivíduos saudáveis dos gêneros masculino e feminino - Garrote Filho, Mario da Silva (2014)
CHAPTER II: The erythrocyte stability is the result of interactions among several factors. Some of them are inherent to the red cell (e.g., the hematimetric indices), whereas others arise from the external environment (e.g., biochemical indices). The present study used path analysis to evaluated how hematological and biochemical indices affect erythrocyte stability under hypotonic stress. The erythrocyte stability was evaluated by the osmotic fragility test, which provided the stability parameters dX and 1/H50. The parameter dX represents the range of NaCl concentration necessary to promote 100% hemolysis and 1/H50 correspond to the inverse of the salt concentration in which there was 50% hemolysis. Both these stability parameters correlated more significantly with the hematological variables, markedly with the Red Cell Distribution width (RDW). Positive correlations were observed for dX and 1/H50 with the RDW and negative correlations were observed between dX and the values of mean corpuscular hemoglobin (MCH) and volume (MCV) of erythrocytes. These results are probably related to the erythrocytes life cycle and may help to shed some light on the mechanisms underlying the ability that elevated values of RDW have regarding the prognosis of many pathological conditions. CHAPTER III: Through experiments in hypotonic media, various osmotic stability parameters of erythrocytes from women with different ages were obtained. These parameters included: 1/H50, which is the inverse of that salt concentration in which there was 50% hemolysis; dX, which is the salt concentration range that extends from the beginning to the end of the hemolysis transition; and Amin, which corresponds to the absorbance value before the hypotonic hemolysis. We also evaluated hematological and biochemical indices of each of the blood samples analyzed. Through path analysis it was found that an increase in the age of the individual is associated with a decrease in osmotic stability of erythrocytes, since age has negative indirect effects on dX and Amin. Menopause, presumed from the age of the study participants, exerts distinct moderation on the direct effect of parameters that influence osmotic stability in women aged 50 years or older compared to those under the age of 50 years. Furthermore, RDW has a positive direct effect on 1/H50 in the menopaused women, but not in those that have not reached this physiological condition.